15.1k views
1 vote
Encuentra en cada producto notable el error o errores,enciérralo y escribe el resultado correcto.

Encuentra en cada producto notable el error o errores,enciérralo y escribe el resultado-example-1

1 Answer

7 votes

Given:

The equation is:


(2x+3y)(2x-3y)=4x^2+6y^2

To find:

The error in the given equation and correct it.

Solution:

We have,


(2x+3y)(2x-3y)=4x^2+6y^2

Taking left-hand side, we get


L.H.S.=(2x+3y)(2x-3y)


L.H.S.=(2x)^2-(3y)^2
[\because a^2-b^2=(a-b)(a+b)]


L.H.S.=(2)^2(x)^2-(3)^2(y)^2
[\because (ab)^x=a^xb^x]


L.H.S.=4x^2-9y^2

It is not equal to right-hand side
4x^2+6y^2. In the right hand side, there must be a negative sign instead of positive sign.

Therefore,
(2x+3y)(2x-3y)=4x^2-6y^2.

User Sromku
by
6.3k points